Responsibility of Medical Personnel in Performing Emergency Actions Related to the Legal Interests of Legal Subjects - Ritonga, Widia Hafsyah Sumarlina; Ravena, Dey; Rahim, Agus Hadian (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Professional standards for medical personnel define the competencies that medical personnel can be held accountable for when practicing medicine. The purpose of these professional standards is to ensure that medical personnel possess a minimum standard of knowledge, skills, and professional behavior, which is also used by relevant parties as a guideline, reference, basis, and guidance in regulating and fostering the medical and dental professions. However, in the cases of Supreme Court Decisions Number 1145K/Pdt/2017 and Number 365K//Pid/2012, medical personnel were faced with an emergency that forced them to perform medical procedures deemed to violate these professional standards. Method: This study uses a descriptive analytical juridical method to analyze the criminal law liability of medical personnel. Data were collected from laws, related regulations, and court decisions. Data analysis was carried out using a qualitative juridical approach. Discussion: The professional standards for doctors are regulated by the Decree of the Indonesian Medical Council Number 193/KKI/KEP/VIII/2024, and the professional standards for dentists are regulated by the Decree of the Indonesian Medical Council Number 126/KKI/KEP/III/2024. These professional standards govern medical personnel in providing healthcare services, including emergency measures. While emergencies are not explicitly stated in Article 48 of the Indonesian Criminal Code and Law Number 1 of 2023 concerning the Indonesian Criminal Code (KUHP), Article 33, is not explicitly stated. However, through doctrine and jurisprudence, the view has developed that emergencies are part of relative coercive power, but not psychological coercive power. Therefore, legal subjects may be faced with three conflicting options. Emergencies can be linked to Article 48 of the Indonesian Criminal Code concerning coercive power and forced circumstances, which can serve as justification and excuse. Conclusion: The liability of medical personnel for performing emergency actions and errors, if carried out in an emergency to protect the patient's life, can be grounds for eliminating criminal penalties for medical personnel and cannot be accounted for.